Local Wisdom of Religion, Culture and Economy of the Community of Kampung Dukuh, Garut, West Java - Ira Siti Rohmah Maulida; Mamat Rachmat Effendi; Ifa Hanifia Senjiati (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
This study describes how the interdependence of religion and culture on the economy of the indigenous people of Kampung Dukuh. The indigenous community of Kampung Dukuh has its uniqueness when compared to other indigenous communities, especially in terms of “religiousness expressed in local wisdom.” The indigenous people of Kampung Dukuh tend to make "religion" as something very basic in their life "the ultimate concern". The study focused on variables, namely (1) Religious Expression; (2) Religious Patterns; (3) Conservation (maintenance, rescue, and protection) of religious values in the indigenous people of Kampung Dukuh, and (4) Economics of the people of Kampung Dukuh This study uses a phenomenological, interpretive, and ecological approach.